Composition for enhancing hair growth. - Mohamed, Suhaila; Roslan Tan, Roslina Tan; Fard, Samaneh Ghasemi (2009)

(untitled)
The present invention discloses a composition to be orally administered or tropically applied for enhancing hair growth and preventing baldness disorder, comprising an extract of vegetative parts of seaweeds, Arecaceae plants family and/or extracts from the group consist in goh honey, green tea, grape seed hibiscus and mixtures thereof.